Influência da neurotransmissão medida pelo óxido nítrico no núcleo dorsal da rafe em modelos animais de ansiedade e depressão - Spiacci Junior, Ailton (2007)
The dorsal raphe nucleus (DRN) has been considered an important component of the brain circuit that mediates anxiety- and depression-related behaviors. High densities of nitric oxide (NO)-producing neurons have been reported in the (NDR). The aim of this study was to evaluate the effects produced by direct administration of the NO precursor L-Arginine, the NOS inhibitor, L-NAME or the cGMP analogue, 8-Br-cGMP, into the DRN of rats submitted to the elevated plus maze (EPM) and the forced swim test (FST) and open field. Male Wistar rats (n=8-12/group) received intra-DRN microinjections of the drugs or saline and, 10 min later, were submitted to the behavioral tracing. L-Arginine (100 and 200 nmol) increased the percentage of time spent in the open arms of the EPM while the administration of NOS inhibitor LNAME (400 nmol) and the cGMP analogue 8-Br-cGMP (25 and 50 nmol) decreased and increased, respectfully, the general motor activity of the animals. Antidepressantlike effects, characterized by a decrease in the immobility time, were observed with lower doses of L-Arginine (50 nmol) or 8-Br-cGMP (12.5 and 25 nmol) in the FST. An opposite effect was observed with L-NAME (100 and 200 nmol). Measurement of the open field test have demonstrated that these drugs interfere with locomotor activity. The behavioral effects can be linked to NO production in the DRN since the effect of L-NAME was counteracted by the injection of L-Arginine. The results suggest that NO may influence motor- and anxiety- related behaviors in the DRN. Further studies are needed to elucidate the mechanism involved in these effects and to address the question if it can also change depressive-like changes independently of motor effects.